Los créditos sin garantía y su influencia en la rentabilidad de las empresas comerciales de fertilizantes de Limoncarro, Año 2018 - Cieza Terán, Stalin Alexander (2019)
This research work refers to the study of unsecured loans and their influence on the profitability of Limoncarro fertilizer trading companies, year 2018, the main objective that is proposed is to determine how unsecured loans granted influence the Profitability of the Fertilizer Marketing Companies of Limoncarro, in relation to the population and the sample is considering the respective companies and workers, as well as the information of economic and financial nature of them, with their techniques and instruments of collection of mentioned data. The main result obtained is that of having determined the relationship that exists between the research variables, that is to say, unsecured loans negatively affect the profitability of these companies, manifested in the accounts receivable and the delinquency itself. Therefore, the main conditional is to have verified that unsecured loans affect the profitability of said Limoncarro Fertilizer Marketing Companies in 2018, according to the evidence presented. The main conclusion that has been obtained is that unsecured loans have a negative influence on the profitability of companies that sell Limoncarro fertilizer.